IMPACTO DE LA IVERMECTINA SOBRE EL AMBIENTE - Aparicio-Medina, Manuel José; Paredes-Vanegas, Varinia; González-López, Odalys; Navarro-Reyes, Omar (La Calera, 2012)
DOI: http://dx.doi.org/10.5377/calera.v11i17.780 La Calera Vol.11 No.17, p.64-66